Health promotion activity in Kampung Tempurunng, Kuala Penyu - Naing Oo Tha; Mazlinda Musa; Vivi Gloria Jinik; Mayrollanizah Douni; Naila Amalia Alexander Liew Seng Yung; Norsheila Ying Ying Karim; Ong, Sheng Yang; Siau, Yee Shing; Tineskumar Gunasagaran Vanitha Kulothungan; Sazeera Suraya Suaan; Zainul Afirin Tanjui (Universiti Malaysia Sabah, 2014)
No abstract